Computational Fluid Dynamics (CFD) Study on Air Flow of Air Diffuser in a Room - m a elfaghi, abdulhafid; Leong, Jeffrey (Research Progress in Mechanical and Manufacturing Engineering, 2023)
The objective of this study is to identify different types of air diffusers and evaluate the performance of 4-blades, 5-blades and proposed 7-blades round ceiling air diffusers and outlet position. Then compare the performance of each type of diffuser and outlet position in terms of air flow behavior and temperature distribution. The scope of my study is that the models will be draft, meshed, and simulated for their air flow behavior and temperature distribution using ANSYS FLUENT. The expected result would be that the diffuser with more blades is expected to provide the room a consistent air flow due to more blades mean more deflection of air. Also, diffuser with more blades is expected to provide better thermal distribution to the room. An outlet near ceiling of the wall could help achieve optimal thermal comfort environment.